FOLLOW-UP OF ISLAMIC EDUCATIONAL INSTITUTIONS, DEEP LEARNING AND AI, THE CONCEPT PF LOCAL WISDOM, A LOVE-BASED CURRICULUM IN ISLAMIC ELEMENTARY SCHOOL - Azzahra, Nafa; Ardana; Arimurti, Ilham; Zainuri, Ahmad; Fatimah Zahra, Frika (International Journal of Multidisciplinary Reseach, 2025)
This article discusses the follow-up to the development of Islamic educational institutions in integrating Deep Learning and Artificial Intelligence (AI) technology with the concept of local wisdom and a love-based curriculum in Madrasah Ibtidaiyah (MI). This approach emphasizes the humanization of education through the values ​​of compassion, spirituality, character, and the use of adaptive technology for personalized learning. Literature research was conducted by reviewing journals, books, and scientific reports from the last ten years. The analysis results indicate that the integration of AI–Deep Learning can improve the effectiveness of learning, automated assessment, personalization of materials, and strengthening character education based on local wisdom. This article presents a conceptual framework, implementation plan, learning design, module examples, lesson plans, syllabi, portfolio rubrics, and operational recommendations for madrasahs.